TINJAUAN YURIDIS KEABSAHAN MATA UANG CRYPTO (CRYPTOCURRENCY) BERDASARKAN PERSPEKTIF UNDANG-UNDANG NOMOR 7 TAHUN 2011 TENTANG MATA UANG - Cucumandalin, I Ketut Samuel; ardhya, si ngurah; Adnyani, Ni Ketut Sari; Kusuma, Putu Riski Ananda (Jurnal Ilmu Hukum Sui Generis, 2024)
This study aims (1) to analyze legal arrangements regarding cryptocurrencies as a reference in providing legal certainty for the use of cryptocurrency in Indonesia, (2) identify the validity of cryptocurrencies based on the perspective of Law Number 7 of 2011 concerning Currency.The type of Penlitain used by researchers is normative legal research, namely through a statutory approach, and a conceptual approach. The sources of legal materials used are the 1945 Constitution, Civil Code, PERPRES, Permendagri, Bappebti, and PBI. The results showed that (1) Juridically normatively, Indonesian law already has provisions or regulations regarding "crypto money". This shows that the government has the awareness to create the rule of law in a new atmosphere of the development of human economic activities in the digital era. It's just that in its normative provisions, there are still conflicting perspectives in looking at crypto money. (2) The legality of using Bitcoin as a medium of exchange to replace rupiah in Indonesia is an illegal payment. In terms of the perspective of Indonesian law, it should be clear that the legitimacy of Bitcoin should not be used as a medium of exchange in e-commerce transactions in Indonesia and/or marketed in Indonesia. However, the Indonesian government through (Bappebti) has established and legalized cryptocurrency as a commodity asset that can be traded on the Futures Exchange as a Crypto Asset. Keywords: currency, crypto, legality.